Methods in calculus.

Slides:



Advertisements
Similar presentations
The Further Mathematics network
Advertisements

U2 L8 Chain and Quotient Rule CHAIN & QUOTIENT RULE
The Chain Rule Section 3.6c.
Calculus CALCULUS Ideas from C3 you may need to know: –differentiation: the product rule –the quotient rule (in formula book) –chain rule, e.g. differentiate.
4.7 Inverse Trig Functions. Does the Sine function have an inverse? 1.
3.5 Inverse Trigonometric Functions
Copyright © Cengage Learning. All rights reserved. 6 Inverse Functions.
CHAPTER Continuity Integration by Parts The formula for integration by parts  f (x) g’(x) dx = f (x) g(x) -  g(x) f’(x) dx. Substitution Rule that.
SECTION 6-D Inverse Trig Derivatives. Inverse Trig functions.
7.3* The Natural Exponential Function INVERSE FUNCTIONS In this section, we will learn about: The natural exponential function and its properties.
Tangents and Normals The equation of a tangent and normal takes the form of a straight line i.e. To find the equation you need to find a value for x, y.
CHAPTER Continuity Implicit Differentiation.
4.7 Inverse Trig Functions. By the end of today, we will learn about….. Inverse Sine Function Inverse Cosine and Tangent Functions Composing Trigonometric.
The General Power Formula Lesson Power Formula … Other Views.
3.5 – Implicit Differentiation
Inverse Trig Functions Tonight’s HW: 3.7 p.483, 5, 6, 13, 23, 25, 31.
ANSWERS. Using Trig in every day life. Check Homework.
Inverse Trig Functions Vocabulary Inverse Cosine Function (cos -1 ) – The function y=cos -1 x = Arccos x, if and only if x = cos y and 0 ≤ y ≤ π Inverse.
Calculus Review. Chapter 1 What is a function Linear Functions Exponential Functions Power Functions Inverse Functions Logs, ln’s and e’s Trig functions.
Lesson 3-6 Implicit Differentiation. Objectives Use implicit differentiation to solve for dy/dx in given equations Use inverse trig rules to find the.
Arcsin, Arccos, Arctan Paul Nettleton. Derivatives of Inverse trigonometric functions.
3.5 Inverse Trigonometric Functions
Copyright © Cengage Learning. All rights reserved.
Derivatives of Inverse Trigonometric Functions. Integrals.
5.8 Inverse Trig Functions and Differentiation
6.8 – Trig Inverses and their graphs
Section 4.7 Inverse Trigonometric Functions
Warm Up Let g(x) = {(1, 3), (2, 5), (4, 10), (-3, 7)}. What is g -1(x)? Write the inverse of the function: f(x) = 2x – 3 Determine whether the function.
6.6 Inverse Trigonometric Functions
Copyright © Cengage Learning. All rights reserved.
Integration By parts.
Trig Graphs And equations.
Trig addition formulae
7.2 – Trigonometric Integrals
5-6 Derivatives of Inverse Trig Functions
Bell work: Find the missing side for the triangles below
Trigonometry Inverse functions
Integration.
Integration review.
The General Power Formula

Parametric equations Problem solving.
5.8 Inverse Trig Functions and Differentiation
Methods in calculus.
Trig Equations.
Copyright © Cengage Learning. All rights reserved.
Integration.
Methods in calculus.
Methods in calculus.
Principal Values of the Inverse Trig Functions
Roots of polynomials.
Integration Volumes of revolution.
Integration Volumes of revolution.
The Inverse Trig FCTNS Function: y = arcsin x y = arccos x
Derivatives of Inverse Trig Functions
Hyperbolic functions.
Integration Volumes of revolution.
Methods in calculus.
Methods in calculus.
Trig Graphs And equations Revision.
Implicit differentiation
Roots of polynomials.
Group Thinking – CIC Problem
x x HW 13: Inverse Trig Functions HW 13: Inverse Trig Functions
Determinant Of matrices.
Calculus 3-7 CHAIN RULE.
Methods in calculus.
Hyperbolic functions.
Hyperbolic functions.
Inverse Trig Functions Rita Korsunsky.
Presentation transcript:

Methods in calculus

FM Methods in Calculus: inverse trig functions KUS objectives BAT differentiate and integrate inverse trig functions using techniques from A2 Starter: find 𝒅𝒚 𝒅𝒙 in terms of x and y for the following 𝑑𝑦 𝑑𝑥 =− 𝑥 𝑦 𝑥 2 + 𝑦 2 =1 5 𝑥 2 +𝑥𝑦+2 𝑦 2 =11 𝑑𝑦 𝑑𝑥 = 10𝑥+𝑦 𝑥+4𝑦 𝑥= tan 𝑦 𝑑𝑦 𝑑𝑥 = 1 𝑠𝑒𝑐 2 𝑦

cos y× dy dx = 1 = 1 𝑐𝑜𝑠 2 𝑦 = 1 1− 𝑠𝑖𝑛 2 𝑦 = 1 1− 𝑥 2 dy dx = 1 cos 𝑦 WB C1 a) show that 𝑑 𝑑𝑥 arcsin 𝑥 = 1 1− 𝑥 2 Let y= arcsin 𝑥 Then sin y=sin arcsin 𝑥 =𝑥 Differentiate implicitly cos y× dy dx = 1 Rearrange and use identity = 1 𝑐𝑜𝑠 2 𝑦 = 1 1− 𝑠𝑖𝑛 2 𝑦 = 1 1− 𝑥 2 dy dx = 1 cos 𝑦 Now b) show that 𝑑 𝑑𝑥 arccos 𝑥 =− 1 1− 𝑥 2 and c) show that 𝑑 𝑑𝑥 arc𝑡𝑎𝑛 𝑥 = 1 1+ 𝑥 2

−sin y× dy dx = 1 =− 1 𝑠𝑖𝑛 2 𝑦 =− 1 1− 𝑐𝑜𝑠 2 𝑦 =− 1 1− 𝑥 2 C1 (cont) b) show that 𝑑 𝑑𝑥 arccos 𝑥 =− 1 1− 𝑥 2 Let y= arccos 𝑥 Differentiate implicitly Then cos y=𝑥 −sin y× dy dx = 1 Rearrange and use identity =− 1 𝑠𝑖𝑛 2 𝑦 =− 1 1− 𝑐𝑜𝑠 2 𝑦 =− 1 1− 𝑥 2 dy dx =− 1 sin 𝑦 C1 c) show that 𝑑 𝑑𝑥 arc𝑡𝑎𝑛 𝑥 = 1 1+ 𝑥 2 Let y= arctan 𝑥 Then tan y=𝑥 Differentiate implicitly 𝑠𝑒𝑐 2 𝑦× dy dx = 1 Rearrange and use identity 𝑡𝑎𝑛 2 𝑦+1= 𝑠𝑒𝑐 2 𝑦 dy dx = 1 𝑠𝑒𝑐 2 𝑦 = 1 𝑡𝑎𝑛 2 𝑦+1 = 1 1+ 𝑥 2

cos y× dy dx = 2𝑥 = 2𝑥 1− 𝑠𝑖𝑛 2 𝑦 = 2𝑥 1− 𝑥 4 dy dx = 2𝑥 cos 𝑦 WB C2 Given 𝑦= arcsin 𝑥 2 , find 𝑑𝑦 𝑑𝑥 a) Using implicit differentiation Using the chain rule and the formula for 𝑑 𝑑𝑥 arcsin 𝑥 a) Let y= arcsin 𝑥 2 Then sin y=sin arcsin 𝑥 2 = 𝑥 2 Differentiate implicitly cos y× dy dx = 2𝑥 Rearrange and use identity = 2𝑥 1− 𝑠𝑖𝑛 2 𝑦 = 2𝑥 1− 𝑥 4 dy dx = 2𝑥 cos 𝑦 b) Let t= 𝑥 2 then y= arcsin 𝑡 Differentiate parametric equations Then dt dx =2𝑥 and dy dt = 1 1− 𝑡 2 use chain rule So dy dx = dt dx × dy dt =2𝑥× 1 1− 𝑡 2 So dy dx = 2𝑥 1− 𝑥 4

NOW DO EX 3C 𝑠𝑒𝑐 2 𝑥 d𝑦 𝑑𝑥 = −2 (1+𝑥) 2 dy dx = 1 𝑠𝑒𝑐 2 𝑥 × −2 (1+𝑥) 2 WB C3 Given 𝑦= 1−𝑥 1+𝑥 find 𝑑𝑦 𝑑𝑥 Let tan y= 1−𝑥 1+𝑥 Differentiate RHS implicitly and LHS by quotient rule 𝑠𝑒𝑐 2 𝑥 d𝑦 𝑑𝑥 = 1+𝑥 −1 −(1−𝑥)(1) (1+𝑥) 2 𝑠𝑒𝑐 2 𝑥 d𝑦 𝑑𝑥 = −2 (1+𝑥) 2 Rearrange and use identity dy dx = 1 𝑠𝑒𝑐 2 𝑥 × −2 (1+𝑥) 2 = 1 1+ 𝑡𝑎𝑛 2 𝑥 × −2 (1+𝑥) 2 dy dx = 1 1+ 1−𝑥 1+𝑥 2 × −2 (1+𝑥) 2 =…= (1+𝑥) 2 2+2 𝑥 2 × −2 (1+𝑥) 2 𝑑𝑦 𝑑𝑥 = −1 2+2 𝑥 2 NOW DO EX 3C

WB D1 By using an appropriate substitution, show that 1 𝑎 2 − 𝑥 2 𝑑𝑥= arcsin 𝑥 𝑎 +𝐶 where a is a positive constant and 𝑥 <𝑎 1 𝑎 2 − 𝑥 2 𝑑𝑥= 1 𝑎 2 1−− 𝑥 𝑎 2 𝑑𝑥= = 1 𝑎 1 1− 𝑥 𝑎 2 𝑑𝑥 𝑢= 𝑎 𝑥 𝑑𝑢= 1 𝑎 𝑑𝑥 = 1 𝑎 1 1− 𝑢 2 𝑑𝑥 = arcsin 𝑢 +𝐶 = arcsin 𝑥 𝑎 +𝐶

WB D1 (cont) By using an appropriate substitution, show that a) 1 𝑎 2 − 𝑥 2 𝑑𝑥= arcsin 𝑥 𝑎 +𝐶 where a is a positive constant and 𝑥 <𝑎 1 𝑎 2 − 𝑥 2 𝑑𝑥= 1 𝑎 2 1−− 𝑥 𝑎 2 𝑑𝑥= = 1 𝑎 1 1− 𝑥 𝑎 2 𝑑𝑥 𝑢= 𝑥 𝑎 𝑑𝑢= 1 𝑎 𝑑𝑥 = 1 1− 𝑢 2 𝑑𝑢 = arcsin 𝑢 +𝐶 = arcsin 𝑥 𝑎 +𝐶 Now show that b) 1 𝑎 2 + 𝑥 2 𝑑𝑥= 1 𝑎 arctan 𝑥 𝑎 +𝐶

WB D1 (cont) By using an appropriate substitution, show that b) 1 𝑎 2 + 𝑥 2 𝑑𝑥= 1 𝑎 arctan 𝑥 𝑎 +𝐶 where a is a positive constant and 𝑥 <𝑎 1 𝑎 2 + 𝑥 2 𝑑𝑥= 1 𝑎 1 1+ 𝑥 𝑎 2 𝑑𝑥= 𝑢= 𝑥 𝑎 𝑑𝑢= 1 𝑎 𝑑𝑥 = 1 𝑎 1 1+ 𝑢 2 𝑑𝑢 = 1 𝑎 arctan 𝑢 +𝐶 = 1 𝑎 arctan 𝑥 𝑎 +𝐶

WB D2 Find 4 5+ 𝑥 2 𝑑𝑥 4 5+ 𝑥 2 𝑑𝑥= 4 1 5+ 𝑥 2 𝑑𝑥 𝑎 2 =5 1 𝑎 2 − 𝑥 2 𝑑𝑥= arcsin 𝑥 𝑎 +𝐶 1 𝑎 2 + 𝑥 2 𝑑𝑥= 1 𝑎 arctan 𝑥 𝑎 +𝐶 4 5+ 𝑥 2 𝑑𝑥= 4 1 5+ 𝑥 2 𝑑𝑥 𝑎 2 =5 =4 1 5 arctan 𝑥 5 +𝐶 = 4 5 arctan 𝑥 5 +𝐶

WB D3 Find 1 25+9 𝑥 2 𝑑𝑥 1 𝑎 2 − 𝑥 2 𝑑𝑥= arcsin 𝑥 𝑎 +𝐶 1 𝑎 2 + 𝑥 2 𝑑𝑥= 1 𝑎 arctan 𝑥 𝑎 +𝐶 𝑎 2 = 25 9 1 25+9 𝑥 2 𝑑𝑥= 1 9 1 5 3 2 + 𝑥 2 𝑑𝑥 = 1 9 1 5 3 arctan 𝑥 5 3 +𝐶 = 1 15 arctan 3𝑥 5 +𝐶

WB D4 Find − 3 /4 3 /4 1 3−4 𝑥 2 𝑑𝑥 𝑎 2 = 3 4 − 3 /4 3 /4 1 3−4 𝑥 2 𝑑𝑥 1 𝑎 2 − 𝑥 2 𝑑𝑥= arcsin 𝑥 𝑎 +𝐶 1 𝑎 2 + 𝑥 2 𝑑𝑥= 1 𝑎 arctan 𝑥 𝑎 +𝐶 𝑎 2 = 3 4 − 3 /4 3 /4 1 3−4 𝑥 2 𝑑𝑥 = 1 2 − 3 /4 3 /4 1 3 4 − 𝑥 2 𝑑𝑥 = 1 2 arcsin 𝑥 3 2 3 /4 − 3 /4 = 1 2 arcsin 1 2 − arcsin − 1 2 = 𝜋 6

NOW DO EX 3D WB D5 Find 𝑥+4 1−4 𝑥 2 𝑑𝑥 𝑎 2 = 1 4 1 𝑎 2 − 𝑥 2 𝑑𝑥= arcsin 𝑥 𝑎 +𝐶 1 𝑎 2 + 𝑥 2 𝑑𝑥= 1 𝑎 arctan 𝑥 𝑎 +𝐶 𝑎 2 = 1 4 𝑥+4 1−4 𝑥 2 = 𝑥 1−4 𝑥 2 + 4 1−4 𝑥 2 𝑥 1−4 𝑥 2 𝑑𝑥 =− 1 8 1 𝑢 𝑑𝑢 𝑢=1−4 𝑥 2 𝑑𝑢=8𝑥 𝑑𝑥 =− 1 4 𝑢 1 2 +𝐶 = − 1 4 1−4 𝑥 2 +𝐶 4 1 1−4 𝑥 2 𝑑𝑥 =2 1 1 4 − 𝑥 2 𝑑𝑥 =2 arcsin 2𝑥 +𝐶 𝑥+4 1−4 𝑥 2 𝑑𝑥=− 1 4 1−4 𝑥 2 +2 arcsin 2𝑥 +C NOW DO EX 3D

One thing to improve is – KUS objectives BAT differentiate and integrate inverse trig functions using techniques from A2 self-assess One thing learned is – One thing to improve is –

END